(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Quality of semen is very important during intrauterine insemination. Objectives: The purpose of the present study was to observe the changes of quality of semen after swim up method during intrauterine insemination. Methodology: This analytical type of cross-sectional study was carried out at a private infertility centre (Central Hospital Limited, Dhaka) in Dhaka city of Bangladesh from January 2012 to December 2017 for a period of 6 years. Infertile couples who already had undergone natural cycles of super-ovulation for six months or whose duration of infertility was more than one year were included. Semen samples were collected by the process of masturbation in semen production room after three days of abstinence in sterile, labelled container. After production all samples were placed in an incubator at 37 degrees Celsius for 30 minutes for liquefaction. Routine semen analysis was performed using World Health Organizations’ (WHO) semen analysis criteria. Then the samples were randomly assigned to be processed either with swim-up or density-gradient procedure. Result: A total number of 789 male respondents were recruited for this study. The mean age with SD of the study population was 28.96±5.382 with the range of 19 to 46 years. The mean changes of sperm concentration before and after swim up method was 52.70±42.88 with the 95% confidence of 49.58 to 55.82 (p=0.000). The mean changes of sperm motility before and after swim up method was 29.03±14.849 with the 95% confidence of 30.11 to 27.95 (p=0.000). The mean changes of sperm morphology before and after swim up method was 23.96±11.328 (p=0.000). Conclusion: There is a significant changes of quality of semen after swim up method during intrauterine insemination Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 54-57